Beyond Classical Fiqh: Sa'ad al-Dīn al-'Uthmānī's Ijtihādī Methodology in Islamic Constitutional Jurisprudence - Abdul Azis, Fakih; Az-Zuhri, Muhammad (Al-'Adl, 2026)
This article examines Sa'ad al-Dīn al-'Uthmānī's contribution to Islamic constitutional jurisprudence through qualitative, analytical-descriptive analysis of his books, peer-reviewed articles, and political speeches. The study addresses a significant research gap by moving beyond existing ideological critiques to systematically reconstruct his constitutional vision and its juristic foundations. Employing thematic coding, the research maps his arguments onto core dimensions of constitutional thought, including sources of political authority, the distinction between religious and political communities, and the protection of rights. The findings demonstrate that al-'Uthmānī rejects the notion of a fixed "Islamic political system" and instead conceptualises state structure as an ijtihādī domain grounded in maqāṣid al-sharī'ah. He reinterprets Khilāfah as a contingent historical construct and affirms the compatibility of Islam with a civil, democratic state based on popular consent, rule of law, equality, and citizenship. His approach, which distinguishes between religious and political communities, sharī'ah and positive law, religious and civil legislation, and Islamic principles versus historical manifestations, offers a maqāṣid-oriented framework that bridges da'wah and political activism, tradition and modernity. The article concludes that al-'Uthmānī provides a coherent model for articulating Islamic constitutional jurisprudence in plural, democratic contexts, while identifying the need for future empirical and comparative research on the practical application and contestation of his ideas.